Fodder for change: animals, urbanisation, and socio-economic transformation in protohistoric Italy - Trentacoste, A (Open Library of Humanities, 2020)
In central and northern Italy, the first millennium BC was characterised by the rise of urbanism and an expansion of nearly every area of production. Agriculture was no exception, and an increase in the scale and intensity of agricultural production sustained, and was sustained by, economic and population growth. Within this context, animal management also evolved to meet the needs of the changing protohistoric landscape. Pigs grew in importance as meat producers, and a greater emphasis was placed on animal-derived products like wool. These changes can be linked to the subsistence requirements of urban populations and the value of raw materials; however, beyond these functional explanations, the wider socio-economic context of animal husbandry is rarely explored.